Effects of foliar application of micronutrients on concentration and bioavailability of zinc and iron in wheat landraces and cultivars - Baozhen Hao (Nature Portfolio, 2021)
Abstract Foliar application of micronutrient is a rapid and promising strategy to enhance the concentration and bioavailability of micronutrients in wheat grain. To explore the effects of foliar application of micronutrients on the concentration and bioavailability of zinc and iron in grain in wheat cultivars and landraces, field experiments were carried out using 65 wheat cultivars and 28 landraces to assess the effects of foliar application of zinc (iron) on phytic acid concentrations, zinc (iron) concentrations and their molar ratios. The results indicated that mean grain zinc concentration of landraces (44.83 mg kg−1) was 11.13% greater than that of cultivars (40.34 mg kg−1) on average across seasons, while grain iron concentration did not differ significantly between landraces (41.00 mg kg−1) and cultivars (39.43 mg kg−1). Foliar zinc application significantly improved the concentration and bioavailability of zinc in grains in both cultivars and landraces, while landraces had almost two-fold more increase in grain zinc and also greater improvement in zinc bioavailability compared to cultivars. While foliar iron application did not significantly affect iron concentration and bioavailability in grains in either cultivars or landraces. Our study showed that, with foliar application of zinc but not iron, wheat landraces had better performance than cultivars in terms of the increases in both concentration and bioavailability of micronutrient in grains.